Current aspects of the problem of "The Bible and Russian literature" - Абрамович, Семен (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The article analyzes the problem of studies of Russian literature in the context of post-Renaissance processes in world, especially in Europe. The Enlightenment program was aimed at undermining the earlier culture and the construction of a new type of culture, in which the centre of attention was the experience of individuals not corrupted by civilization and Christian morality. The apogee of this cult of the creative «I» lies in the romanticism of his titanic «rebellion» against God. But Russian literature, as well as other Eastern Slavic literature, is based on the Christian books, which were its original sources. The secularization of culture after Peter I was aimed to destroy this base. However it was preserved and eventually evolved into the idea of communist totalitarianism. Therefore, the realization of the Enlightenment project – the creation of popular culture in Russia was particularly devastating. Russian classic output stems from the Christian tradition. It should be recognized that the artistic word cannot properly «educate», which is the function of didactic or sacred books.